2021
DOI: 10.1080/26395940.2021.1932605
|View full text |Cite
|
Sign up to set email alerts
|

Transport of micro/nano biochar in quartz sand modified by three different clay minerals

Abstract: Biochar has received continuous attention in recent years due to its high specific surface area, rich micropores, and many types of functional groups. In this study, the migration behavior of modified micro-nano biochar (MMNBC) in heterogeneous media under the influence of ionic strength and flow rate was studied by column experiments. The results showed that the mobility of MMNBC could be increased by increasing the flow rate and decreasing IS. The retention of MMNBC in quartz sand coated with clay minerals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 31 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Multiple column simulation experiments were previously performed to investigate the effects of hydraulic, porous media properties, solution chemistry, physicochemical properties, and mineral coating of BC-NP on the transport and retention of BC-NP in porous media (Chen et al, 2017;Wang et al, 2019;Liu et al, 2021). The results of these studies showed that BC-NP had high transportability in porous media with low ionic strength and high pore water velocity, or in the presence of natural organic compounds and surfactants.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple column simulation experiments were previously performed to investigate the effects of hydraulic, porous media properties, solution chemistry, physicochemical properties, and mineral coating of BC-NP on the transport and retention of BC-NP in porous media (Chen et al, 2017;Wang et al, 2019;Liu et al, 2021). The results of these studies showed that BC-NP had high transportability in porous media with low ionic strength and high pore water velocity, or in the presence of natural organic compounds and surfactants.…”
Section: Introductionmentioning
confidence: 99%